Pengaruh Faktor Sosial Ekonomi terhadap Tingkat Fertilitas di Kecamatan Tembalang Kota Semarang - Apriwana, Cintami (Universitas Negeri Semarang, 2019)
Fertility is one of the causes of the high population in an area. The problem in this study showed the high level of fertility in Sub-district Tembalang, Semarang, although the population of the District Tembalang is a second largest population after the District Pedurungan. The subjects of this study were heads mother in Sub Tembalang. This study using a sample of 100 respondents of the total population which is 10.600 people The analytical tool used in this study is descriptive analysis and multiple linear regression by using SPSS software version 16.0.The results are obtain socioeconomic variables family income, education, age of first marriage are influential negative and significance on the level of fertility in Sub Tembalang, Semarang. Whereas the variable of working hours is not significant on the fertility rate. Suggestions relating to this study so that the authorities and field officers of PLKB in Sub-District Tembalang, hold a socialization for the society about the importance of marriage age maturation and improvement of education, so that the fertility can be reduced. Fertilitas merupakan salah satu penyebab tingginya jumlah penduduk di suatu daerah. Masalah dalam penelitian ini menunjukkan masih tingginya tingkat fertilitas di Kecamatan Tembalang Kota Semarang, meskipun jumlah penduduk di Kecamatan Tembalang berada pada posisi kedua penduduk terbesar setelah Kecamatan Pedurungan. Subjek penelitian ini ibu rumah tangga yang berada di Kecamatan Tembalang. Penelitian ini menggunakan sampel 100 responden dari keseluruhan jumlah populasi adalah 10.600 orang. Dari hasil penelitian diperoleh variabel sosial ekonomi pendapatan keluarga, pendidikan, usia kawin pertama berpengaruh negatif dan signifikan terhadap tingkat fertilitas di Kecamatan Tembalang Kota Semarang. Sedangkan variabel curah jam kerja tidak berpengaruh signifikan terhadap tingkat fertilitas. Saran yang berkaitan dengan penelitian ini supaya pihak pemerintah dan PLKB di Kecamatan Tembalang mengadakan sosialisasi kepada masyarakat mengenai pentingnya pendewasaan usia pernikahan dan peningkatan pendidikan, sehingga fertilitas dapat berkurang.